Kombinasi Afiks di- dan -kan sebagai Afiks Derivasional dalam Bahasa Indonesia - Hidayati, Mardliyyah; Widyastuti, Chattri Sigit (Department of Languages and Literature, Faculty of Cultural Sciences, UGM, 2026)
This research aims to describe the morphological process of adding the derivational combination affix di- and -kan in Indonesian. This qualitative type of research uses data in the form of sentences containing words with the combination affix di- and -kan. The data sources are the Tempo Magazine (26 August 2024 edition) entitled Jungkir Balik Balik Raja Jawa, Jurnal Ranah volume 12 number 1 in 2023, textbook Sejarah Kelas 12 SMA Kurikulum Merdeka in 2022, and essay collection Nggragas! by Triyanto Triwikromo in 2021. The method for providing data uses the observation method with note-taking techniques, then analyzed sequentially by using the distributional method, immediate constituent, deletion, and expansion techniques. The results of this research are that all the data shows that the combination affix di- and -kan changes the word class into a verb form. The changes that occur are not only changes in word classes and their meanings but some only experience changes in meaning. Changes in word class and meaning occur in changes from noun to verb (N → V), adjective to verb (Adj → V), adverb to verb (Adv → V), numerals to verb (Num → V), conjunction to verb (Conj → V). Changes in meaning occur when active verbs become intensive passive verb, and active verbs become causative passive verb.